Plant DNA banks for genetic resources conservation (review) - Н. Е. Волкова (Plant Varieties Studying and Protection)
Purpose. Literature review of DNA banks creation as the current strategy of plant genetic resources conservation. Results. The current state of plant genetic resources conservation was analyzed in the context of the threat of genetic erosion. The importance of DNA banks was shown which function is to store DNA samples and associated products and disseminate them for research purposes. The main DNA banks in the world were described, including the Republican DNA Bank of Human, Animals, Plants and Microorganisms at the Institute of Genetics and Cytology of the National Academy of Sciences of Belarus. Stages of DNA banking were considered: tissue sampling (usually from leaves), cell destruction, DNA extraction, DNA storage. Different methods of tissue sampling, extraction and DNA storage were compared. The need for Plant DNA Bank creation in Ukraine was highlighted. Conclusions. DNA collections is an important resource in the global effort to overcome the crisis in biodiversity, for managing world genetic resources and maximizing their potential.